Effect of Omeprazole on the Pharmacokinetics of Rosuvastatin in Healthy Male Volunteers. (November 2016) - Shah, Yasar; Iqbal, Zafar; Ahmad, Lateef; Khuda, Fazli; Khan, Abad; Khan, Abbas; Khan, Muhammad Imran; Ismail,
Abstract : The current study aimed at the evaluation of, in vivo, the effect of omeprazole on the pharmacokinetics of rosuvastatin, a 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitor. Omeprazole is an acid suppressant and CYP2C9, CYP3A4, and CYP2C19 substrate and inhibitor, as well as inhibitor of transporters (like P-gp). This was a randomized, open-label, 2-period, crossover study. Healthy male volunteers (N = 20), divided into 2 groups, were given single oral doses of rosuvastatin 40 mg either alone (treatment period I) or concomitantly with omeprazole 40-mg capsule (treatment period II). Plasma concentrations of rosuvastatin (rosuva) and its metabolite N-desmethyl rosuvastatin (NDM-rosuva) were quantified by a validated liquid chromatography–tandem mass spectrometry method developed in our laboratory. An insignificant decrease ( P > 0.05) has been observed in the values of maximum plasma concentrations, clearance, and half-life of rosuva, whereas an insignificant increase ( P > 0.05) has been observed in the area under the plasma concentration–time curves from zero time to the last measurable concentration, that extrapolated to infinity, and mean residence time values after concomitant administration with omeprazole. Although omeprazole concomitant administration altered the pharmacokinetics of NDM-rosuva metabolite significantly, rosuva's very little metabolism (10%) suggests that these changes are of no clinical significance. Concomitant administration of omeprazole with rosuva did not alter the pharmacokinetics of rosuva in healthy volunteers. These data are consistent with other reported studies, indicating that rosuva is not a good candidate for metabolism-based drug–drug interactions. Therefore, rosuva can be administered safely along with omeprazole.